Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the remainder when the polynomial [tex]\( P(x) \)[/tex] is divided by [tex]\( x(x^2 - 1) \)[/tex], follow these detailed steps.
We know that:
1. When [tex]\( P(x) \)[/tex] is divided by [tex]\( x-1 \)[/tex], the remainder is 1.
2. When [tex]\( P(x) \)[/tex] is divided by [tex]\( x \)[/tex], the remainder is 2.
3. When [tex]\( P(x) \)[/tex] is divided by [tex]\( x+1 \)[/tex], the remainder is 3.
We need to express [tex]\( P(x) \)[/tex] in a form that helps us find the remainder when divided by [tex]\( x(x^2 - 1) \)[/tex].
A helpful approach is to write the polynomial [tex]\( P(x) \)[/tex] as:
[tex]\[ P(x) = (x-1)(x)(x+1)Q(x) + ax^2 + bx + c \][/tex]
where [tex]\( Q(x) \)[/tex] is some polynomial and [tex]\( ax^2 + bx + c \)[/tex] is the remainder when [tex]\( P(x) \)[/tex] is divided by [tex]\( x(x^2 - 1) \)[/tex].
Given the remainders, we have three conditions from insertions into [tex]\( P(x) \)[/tex]:
1. [tex]\( P(1) = a(1)^2 + b(1) + c = 1 \)[/tex]
2. [tex]\( P(0) = c = 2 \)[/tex]
3. [tex]\( P(-1) = a(-1)^2 - b(1) + c = 3 \)[/tex]
Using these conditions, we can set up a system of equations:
1. [tex]\( a + b + c = 1 \)[/tex]
2. [tex]\( c = 2 \)[/tex]
3. [tex]\( a - b + c = 3 \)[/tex]
Starting with the second equation directly gives us:
[tex]\[ c = 2 \][/tex]
Substituting [tex]\( c = 2 \)[/tex] into the first and third equations, we get:
1. [tex]\( a + b + 2 = 1 \)[/tex]
2. [tex]\( a - b + 2 = 3 \)[/tex]
Simplifying these equations:
1. [tex]\( a + b + 2 = 1 \)[/tex] simplifies to [tex]\( a + b = -1 \)[/tex]
2. [tex]\( a - b + 2 = 3 \)[/tex] simplifies to [tex]\( a - b = 1 \)[/tex]
Now we have a simpler system of linear equations:
1. [tex]\( a + b = -1 \)[/tex]
2. [tex]\( a - b = 1 \)[/tex]
To solve this system, we can add the two equations:
[tex]\[ (a + b) + (a - b) = -1 + 1 \][/tex]
[tex]\[ 2a = 0 \][/tex]
[tex]\[ a = 0 \][/tex]
Next, substituting [tex]\( a = 0 \)[/tex] into the equation [tex]\( a + b = -1 \)[/tex]:
[tex]\[ 0 + b = -1 \][/tex]
[tex]\[ b = -1 \][/tex]
We have found that:
[tex]\[ a = 0 \][/tex]
[tex]\[ b = -1 \][/tex]
[tex]\[ c = 2 \][/tex]
Thus, the remainder when [tex]\( P(x) \)[/tex] is divided by [tex]\( x(x^2 - 1) \)[/tex] is:
[tex]\[ 0x^2 - x + 2 = -x + 2 \][/tex]
Therefore, the remainder is:
[tex]\[ -x + 2 \][/tex]
We know that:
1. When [tex]\( P(x) \)[/tex] is divided by [tex]\( x-1 \)[/tex], the remainder is 1.
2. When [tex]\( P(x) \)[/tex] is divided by [tex]\( x \)[/tex], the remainder is 2.
3. When [tex]\( P(x) \)[/tex] is divided by [tex]\( x+1 \)[/tex], the remainder is 3.
We need to express [tex]\( P(x) \)[/tex] in a form that helps us find the remainder when divided by [tex]\( x(x^2 - 1) \)[/tex].
A helpful approach is to write the polynomial [tex]\( P(x) \)[/tex] as:
[tex]\[ P(x) = (x-1)(x)(x+1)Q(x) + ax^2 + bx + c \][/tex]
where [tex]\( Q(x) \)[/tex] is some polynomial and [tex]\( ax^2 + bx + c \)[/tex] is the remainder when [tex]\( P(x) \)[/tex] is divided by [tex]\( x(x^2 - 1) \)[/tex].
Given the remainders, we have three conditions from insertions into [tex]\( P(x) \)[/tex]:
1. [tex]\( P(1) = a(1)^2 + b(1) + c = 1 \)[/tex]
2. [tex]\( P(0) = c = 2 \)[/tex]
3. [tex]\( P(-1) = a(-1)^2 - b(1) + c = 3 \)[/tex]
Using these conditions, we can set up a system of equations:
1. [tex]\( a + b + c = 1 \)[/tex]
2. [tex]\( c = 2 \)[/tex]
3. [tex]\( a - b + c = 3 \)[/tex]
Starting with the second equation directly gives us:
[tex]\[ c = 2 \][/tex]
Substituting [tex]\( c = 2 \)[/tex] into the first and third equations, we get:
1. [tex]\( a + b + 2 = 1 \)[/tex]
2. [tex]\( a - b + 2 = 3 \)[/tex]
Simplifying these equations:
1. [tex]\( a + b + 2 = 1 \)[/tex] simplifies to [tex]\( a + b = -1 \)[/tex]
2. [tex]\( a - b + 2 = 3 \)[/tex] simplifies to [tex]\( a - b = 1 \)[/tex]
Now we have a simpler system of linear equations:
1. [tex]\( a + b = -1 \)[/tex]
2. [tex]\( a - b = 1 \)[/tex]
To solve this system, we can add the two equations:
[tex]\[ (a + b) + (a - b) = -1 + 1 \][/tex]
[tex]\[ 2a = 0 \][/tex]
[tex]\[ a = 0 \][/tex]
Next, substituting [tex]\( a = 0 \)[/tex] into the equation [tex]\( a + b = -1 \)[/tex]:
[tex]\[ 0 + b = -1 \][/tex]
[tex]\[ b = -1 \][/tex]
We have found that:
[tex]\[ a = 0 \][/tex]
[tex]\[ b = -1 \][/tex]
[tex]\[ c = 2 \][/tex]
Thus, the remainder when [tex]\( P(x) \)[/tex] is divided by [tex]\( x(x^2 - 1) \)[/tex] is:
[tex]\[ 0x^2 - x + 2 = -x + 2 \][/tex]
Therefore, the remainder is:
[tex]\[ -x + 2 \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.